Mathematical modelling of infrared‐dried kiwifruit slices under natural and forced convection - Sadeghi, Ebrahim (Food Sci Nutr, 2019)
In this work, the effect of the radiation intensity, slice thickness, and the distance between slices and infrared lamps under natural drying air and the effect of slice thickness and air velocity under forced drying air on the moisture diffusion characteristics and the drying rate of kiwifruit slices during infrared drying were investigated. The drying of kiwifruit happened in the falling rate period, and no constant‐rate period was observed in the drying curves. One hundred models were fitted to the drying data. Among the models, the exponential dsecay function model and modified two‐term exponential‐V model and the artificial neural networks with 4‐5‐7‐1 and 3‐5‐5‐1 topologies, hyperbolic tangent sigmoid transfer function, and Levenberg‐Marquardt training algorithm presented the best results and showed the goodness of fit with the experimental data for the former and latter systems, respectively. The diffusivities varied between 1.216 × 10(−10)–8.997 × 10(−10) m(2)⁄s and 2.567 × 10(−10)–10.335 × 10(−10) m(2)⁄s for natural and forced drying air systems, respectively.